The Phenomenon of Early Marriage and its Impact on Family Resilience - Zulfa, Vania; Hasanah, Uswatun; Kusaini, Fitriana (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Early marriage is a marriage that is carried out under the age of 19 and generally does not have the readiness to build a family physically, economically, emotionally and has not thought about the impact of family resilience. The purpose of this study was to determine the background, causal factors and family resilience of early marriage. This research uses a qualitative case study method. There were 12 primary and secondary informants. Data collection techniques used observation, interviews, and document studies. Data analysis uses the theory of Miles and Huberman (1984) and checks the validity of the data by triangulating data sources. The results showed that the background of early marriage was due to a lack of education for the community regarding the impact of early marriage, a feeling of shame for neighbors who were married but themselves were not married, and a feeling of fear of becoming an old maid. The factors of early marriage are fear of causing fitnah, being matched because they have seen a prospective husband who is already working, the condition of parents who are not intact so they cannot afford to pay for children's schooling, the influence of social media and peers. The findings of this study are that early marriages are generally conducted “siri” because of the ease of access compared to official marriages. The level of family resilience of early marriage couples is still vulnerable, especially the legality of family integrity, physical resilience, economic resilience, and socio-psychological resilience.